Penerapan Metode Role playing (Bermain Peran) dalam Upaya Meningkatkan Hasil Belajar Peserta Didik Kelas II tentang Konsep Pembagian pada Mata Pelajaran Matematika di SDN Cempaka Putih 17 Pagi Jakarta Pusat - Estina Meiliana (INTELEKTIUM, 2022)
Mathematics is one of the essential subjects that exists at every level of education, from elementary to high school. Using the right method can make it easier for students to understand the learning material presented. The purpose of this study was to find out whether there was an opening to the learning outcomes of class II students at SDN Cempaka Putih Barat 17 Pagi in mathematics lessons using the Role Playing method. The data source for this study was 36 grade II students at SDN Cempaka Putih Barat 17 Pagi, Cempaka Putih District, Central Jakarta. The research was conducted from 18 February to 18 March 2020. The data collected was qualitative and quantitative. Quantitative data is data taken from the results of formative tests in each cycle while qualitative data is data obtained from teacher observations in each learning cycle. By using the Role Playing method, the student's ability in class II SDN Cempaka Putih Barat 17 pagi in learning mathematics about the concept of division increased significantly. From 36 students in the first cycle, 21 students (58%) understood the concept of division in the second cycle, compared with 10 students (28%) in the first cycle. .